Persistent Continental Shelf Carbon Sink at the Ieodo Ocean Research Station in the Northern East China Sea - Lee, Kitack; Kim, Ja-Myung; Lee, Gyeong-Seok; Lee, Eunil; Jeong, Jin-Yong; Lee, Jaeik; Han, In-Seong (Frontiers in Marine Science, 2022)
Hourly (2017–2021) to seasonal (2015–2021) inorganic C data were collected at the Ieodo Ocean Research Station (32.07°N and 125.10°E) in the northern East China Sea (ECS), located under the influence of the nutrient-rich Changjiang Diluted Water (CDW). An increase in phytoplankton biomass from April to mid-August (the warming period) equalized much of the temperature-driven increase in the surface pCO2 and thus, made the northern ECS a moderate sink of atmospheric CO2. From November to March (the cooling period), a large pCO2 reduction, driven by a temperature reduction, and a high air–sea CO2 exchange rate, because of high windspeeds, transformed the basin into a substantial CO2 sink, yielding an annual net C uptake of 61.7 g C m–2 yr–1. The effects of biological production and temperature change on seawater pCO2 (and thus, the net air–sea CO2 flux) were decoupled each season and acted in concert to increase the net annual CO2 sink by the region. The present study provided the observational and mechanistic lines of evidence for confirming “continental shelf C pump”—a mechanism in the shallow waters of the continental shelves that accumulate a significant amount of C (via reinforced cooling and promoted biological C uptake) that is transported from the basin surface waters to the interior of the adjacent deep ocean. In the future, an increasing input of anthropogenic nutrients into the northern ECS is likely to make the region a stronger CO2 sink.